El aprendizaje escolar significativo en los niños víctimas de violencia intrafamiliar que estudian en el quinto grado en la escuela de educación general básica rosa josefina Burneo de Burneo de la ciudad de Loja 2018-2019 - Oviedo Ochoa, Cinthya Lisseth (2019)
This research work is framed in a study entitled, THE SIGNIFICANT SCHOOL LEARNING IN CHILDREN VICTIMS OF INTRAFAMILIAR VIOLENCE STUDYING IN THE FIFTH GRADE IN THE SCHOOL OF BASIC GENERAL EDUCATION ROSA JOSEFINA BURNEO DE BURNEO OF THE CITY OF LOJA 2018-2019. This research work is framed in a study entitled, THE SIGNIFICANT SCHOOL LEARNING IN CHILDREN VICTIMS OF INTRAFAMILIAR VIOLENCE STUDYING IN THE FIFTH GRADE IN THE SCHOOL OF BASIC GENERAL EDUCATION ROSA JOSEFINA BURNEO DE BURNEO OF THE CITY OF LOJA 2018-2019, whose problematic makes reference to that the children of the fifth grade present characteristics of suffering intrafamiliar violence like: physical violence where the students physically show blows that the parents give them and in the emotional part when indicating that they suffer criticism, ridicule and insults and significant school learning problems such as: They do not pay attention in classrooms, they are easily distracted, they do not fulfill their duties, they are not obedient; likewise, they show attitudes of disrespect among them, such as insults and beatings, there being a significant number of students who come from dysfunctional families where there is violence and abandonment by parents, both in personal, academic and affective care . Among the objectives set out in the research is as a general objective: Proposing Psychoeducational Workshops to strengthen intrafamilial relationships and improve significant school learning in children victims of domestic violence, who study in the Fifth Grade of the School of General Basic Education Rosa Josefina Burneo de Burneo of the City of Loja in the period 2018-2019, which was fulfilled by designing an alternative proposal. We carried out a scientific - social, descriptive research with quantitative - qualitative approach, using diverse methods and instruments such as: scientific method, synthetic - analytical, inductive, deductive and descriptive. The techniques used were: Survey aimed at students, teachers and parents. The instruments used were: Cisneros Questionnaire that allowed to evaluate the type of intrafamilial violence to which children are exposed, as well as the Academic Self-concept Questionnaire to determine the knowledge acquired through the learning of Significant Learning. Among the main conclusions mentioned: The most frequent type of intrafamily violence in the homes of children in the fifth grade is psychological and physical, limiting to achieve significant learning in their school environment